Pharmacological properties of Chebulinic acid and related ellagitannins from nature: An emerging contemporary bioactive entity - Ashwani K. Dhingra; Bhawna Chopra; Ajmer Singh Grewal; Kumar Guarve (Elsevier, 2022)
Terminalia chebula, (Family: Combretaceae) is a medicinally active plant possess a wide spectrum of biological activities and contain numerous bioactive phytoconstituents like phenolic compounds, hydrolysable tannins, and flavonoids, therefore it may be considers as a good therapeutic alternative. Chebulinic acid, an ellagitannin was isolated from the fruits of Terminalia chebula and was known to possess numerous biological activities including anti-tumor activity, anti-atherogenic, anti-fibrotic, anti-inflammatory, antiulcer, antioxidant, hepatoprotective, antidiabetic, and antiviral etc. The present chapter describes the various analytical methods, structure elucidation, biological activities, pharmacokinetic, patents and various marketed formulations. Thus, chebulinic acid and related derivatives of Terminalia chebula and other plant species possess numerous pharmacological which paves way for further studies.